Treatment and Management Experience of Idiopathic Granulomatous Mastitis in a Low-income Country - Pedro Antonio Llancari; Antonio Ortiz; Juan Becerra; Ricardo Muñoz; Christiam Valeriano; Rommy Helena Novoa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective Reporting our experience of the management and treatment of Idiopathic granulomatous mastitis (IGM) in a low-income country by describing patients characteristics and therapy with emphasis on conservative surgical excision and postoperative care as the cornerstone of treatment. Methods A retrospective cohort of women with histopathological diagnosis of IGM from 2014 to 2018 at Instituto Nacional Materno Perinatal in Lima, Peru. Patients' characteristics, clinical presentation, treatment, management, postoperative care, and follow-up were analyzed. Results Thirty-eight patients with histopathological diagnosis of IGM were identified. Their average age was 35.9 years and 23 (60.5%) reported previous use of hormonal contraceptives. Nine (23.7%) patients had chronic mastitis with previous treatment. The time from the onset of symptoms to the first clinic consult was 5.1 months on average. Twenty-one (55.3%) patients had the lesion in the right breast, with a mean size of 6.9 cm. Conservative surgical excision was performed in all patients. Additionally, 86.8% required corticosteroids and 78.9% were treated with antibiotics. Complete remission was obtained at 141 days on average (range 44 to 292 days). Six (15.8%) women reported ipsilateral recurrence and 5 (13.2%), contralateral. The latency time was 25.5 months on average. Conclusion The conservative surgical treatment demonstrated and close follow-up made for a high cure rate, but with recurrence similar to that reported in the literature. Use of gloves is an alternative to manage post operative wounds in a low-income country. The most frequent adverse effect was breast surgical scar.